Predictor Prognosis of Pediatric Septic Shock : Literature review - Nikma Alfi Rosida; Suhendra Suhendra; Berna Detha Meilyana; Rischar Beny Riswanto (Universitas Airlangga, 2022)
Introduction: The unpredictability of body response to organ dysfunction needs an effective tool to predict the prognosis of shock septic. Early recognition and treatment of septic shock improved prognosis and reduced mortality, especially in pediatrics. This review aimed to identify the predictor of mortality in pediatric septic shock. Methods: We performed a literature review of the predictor of mortality in pediatric septic shock conducted between 2015 and 2020 in ProQuest, Google Scholar, PubMed, and Science Direct. We used keywords (predictor or predictive) and (septic shock or septic), and (prognostic or prognosis) and (pediatric or children). The study selection was using the Preferred Reporting Items for Systematic Review and Meta-Analysis PRISMA framework. Results: 944 articles identified in ProQuest, 720 articles in Science Direct, 339 articles in Google Scholar, and 67 in Pubmed. Equally, the total articles were 2,070 articles, and there were 414 duplicates. After review of the complete texts was performed for 35 potential studies. In the full-text review, we excluded review articles (n = 3), different populations (n=8), and of poor quality (n = 20). Eventually, four papers were reviewed in this study. We found PELOD, PELOD-2, PIM, PIM 2, PIM 3, PMODS, PRISM, PRISM-III, PRISM-IV, and pSOFA as a predictor of sepsis in pediatrics. Conclusion: In conclusion, pSOFA is a more accurate screening result for estimating the risk of death by being 10 times more sensitive and specific. However, adding biomarkers to pSOFA will improve the accuracy of the predictor prognosis of pediatric sepsis.